Mechanistic insight and consequence of phosphogunstic acid in corncob hydrolysis process. (September 2020) - Li, Fei; Zhao, Haiping; Zhu, Zheng; Cheng, Liyuan; Yu, Wangning
Abstract: Corncobs were treated with the hydrothermal method using phosphotungstic acid as a catalyst, and furfural and 5-HMF were produced and analyzed using high-performance liquid chromatography (HPLC). The adsorption capacity of corncob residues for methylene blue was also studied. The structure and properties of corncob residues were characterized by the elemental analyzer, X-ray powder diffraction, specific surface analyzer, and scanning electron microscopy. The effects of the dosage of phosphotungstic acid, reaction time, temperature, and solid-liquid ratio on the yields of furfural and 5-HMF were investigated. The yield of furfural reached 26.23% when corncobs were treated with 0.4 g phosphotungstic acid at 160 °C for 4 h. At the same temperature, the smaller solid-liquid ratio could increase the yields of 5-HMF and furfural. The yield of corncob residues varied from 35.95% to 80.80% under different conditions. The adsorption capacity of corncob residues for methylene blue ranged from 9.0 to 57.4 mg/g. Graphical abstract: The phosphotungstic acid was used as a catalyst to treat corncobs under hydrothermal condition. The contents of two major hydrolysates, furfural and 5-HMF, were determined using high-performance liquid chromatography (HPLC). The yield of furfural reached 6.2% when corncobs were treated with 0.4 g phosphotungstic acid at 160 °C for 4 h. The maximum adsorption capacity of corncob residues for methylene blue reached 57.4 mg/g. Unlabelled Image Highlights: Corncobs were hydrothermally treated with phosphotungstic acid. The yield of furfural reached 26.23% at 0.4 g phosphotungstic acid (160 °C, 4 h). Corncob residues have relatively high adsorption capacity for methylene blue.